Comparative reflections on skill and the good life in zhuangzi and stoicism. Issue 2 (2nd April 2020) - Yu, Jiangxia
ABSTRACT: This paper explores the concept of skill in Zhuangzi and Stoicism, and argues that the role of the Stoic techne in practicing the art of living can be better understood if we introduce some perspectives of Zhuangzi's Ji . For Zhuangzi, by manifesting Dao and cultivating virtue, skillful activity can be taken as the spiritual exercise to nourish the art of living with which one can do things with great ease, and achieve spiritual satisfaction. Similarly for the Stoics, by following logos and cultivating virtue, skillful activity can be used to practice the art of living with which one can do everything well consistently and achieve happiness. By highlighting the role of skillful activity in manifesting Dao (or logos ) and obtaining virtue, both Zhuangzi and the Stoics try to nourish an art of living through the practice of professional skills, which makes life a good flow, i.e., spiritual satisfaction or happiness.